Prevalence and distribuion of staphylococcal enterotoxin genes among Staphylococcus aureus isolates from chicken and turkey carcasses in Algeria - Mebkhout, F.; Mezali, L.; Hamdi, T. M.; Cantekin, Z.; Ergun, Y.; Ramdani-Bouguessa, N.; Butaye, P. (Journal of the Hellenic Veterinary Medical Society, 2019)
This study is aimed to determine the prevalence of staphylococcus aureus (S.aureus) by biochemical tests in poultry carcasses. It is also intend to detect the distribution of genes for classical staphylococcal enterotoxins A, B, C, D and E (sea, seb, sec, sed and see) and for gene femA, specific for S.aureus species, using multiplex PCR. A total of 385 samples of neck skins from fresh poultry carcasses were collected during the period 2012-2013 from 16 different slaughterhouses located in the region of Algiers, Algeria. The overall prevalence of S.aureus in freshly slaughtered poultry carcasses was 41.56%, with an individual prevalence of 40.63% and 45.71% for chicken and turkey respectively. From the 95 strains of S.aureus identified by biochemical tests, 82 (86.32%) isolates were femA positive using multiplex PCR. The investigation has also revealed the presence of both enterotoxins B and D, with a predominance of seb (13.33%) followed by sed (1.67%), in the chicken carcasses while in turkey only sed was detected (4.55%) It has been found that strains of S.aureus of poultry origin can be enterotoxigenic with the predominance of genes encoding for enterotoxins seb in chicken and sed in turkey. As enterotoxins can be produced in adequate amounts to induce foodborne illnesses, these potential dangers must be considered in terms of a real risk to public health.